Hubungan Pengetahuan Kewirausahaan Dengan Minat Berwirausaha Di Marketplace Pada Mahasiswa Pendidikan IPS Universitas Negeri Jakarta - Lailati El Fithria; Desy Safitri; Sujarwo Sujarwo (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Entrepreneurial knowledge and interest in entrepreneurship in the marketplace are important factors in shaping the quality of students. Lack of entrepreneurial knowledge in students results in a lack of interest in entrepreneurship. This study aims to explore the relationship between entrepreneurial knowledge and interest in entrepreneurship in the marketplace among Social Studies Education students, Jakarta State University, especially in the 2020 and 2021 intakes. The research method used is correlation research with a quantitative approach. The sample of this study was 118 Social Studies Education students, Jakarta State University, the 2020 and 2021 intakes. Data were collected through a questionnaire that focused on the variables of entrepreneurial knowledge and interest in entrepreneurship in the marketplace with a measurement scale using the Likert scale. Data analysis was carried out using normality tests and correlation tests. The results of the analysis showed that there was a significant relationship between entrepreneurial knowledge and interest in entrepreneurship in the marketplace of Social Studies Education students, Jakarta State University, the 2020-2021 intake. This shows that the better the students' entrepreneurial knowledge, the higher the interest in entrepreneurship in the marketplace of Social Studies Education students, Jakarta State University, the 2020-2021 intake. The relationship between the two variables is included in the high category. The implication of this study is the importance of paying attention to other factors that can also influence entrepreneurial interest.